Marcuse From the New Left to the Next Left - Bokina, John; Lukes, Timothy J. (University Press of Kansas, 1994)
Marcuse brings back to center stage one of the most celebrated and controversial philosophers of the turbulent 1960s, the man Time magazine called the "guru of the New Left."In Reason and Revolution, Eros and Civilization, OneDimensional Man, and other notable works, Herbert Marcuse crystallized the essence of counterculture philosophy. His neoMarxist critique of Western capitalism was widely embraced by revolutionaries, "hippies," and an entire generation of academics who condemned political, economic, and sexual repression in American society. So complete was Marcuse's identification with the New Left that, with its demise, he and his works fell out of favor. But, as this volume persuasively demonstrates, Marcuse remains vitally relevant for us today.Returning to Marcuse may recall the clash of idealistic exuberance and tragic violence associated with Woodstock, HaightAshbury, the Vietnam War, 1968 Democratic Convention, Kent State, and Earth Day, as well as the passionate voices of antiwar and civil rights protesters, environmentalists, feminists, and free love advocates. But this volume does not cater to the simplistic nostalgia of aging babyboomers.Fifteen leading Marcuse scholars, including Marcuse's son Peter, assess the philosopher's ideas in the radically different theoretical and political contexts of the 1990s. The range of topics covered is distinctly contemporary-Foucault and postmodern theories, analytical Marxism and the demise of the Soviet Union, women's studies and feminist psychoanalytic theory, aesthetic consciousness and postmodern art, radical ecology and cybernetic technology-and includes Douglas Kellner's revealing first look at the unpublished manuscripts in the Marcuse Archives in Frankfurt.Sure to excite liberal as well as irritate conservative culture warriors, these provocative essays illuminate the outlines of a Marcuse revival and the Next Left as both emerge to confront the complex challenges of our times.